The Caries Phenomenon: A Timeline from Witchcraft and Superstition to Opinions of the 1500s to Today's Science - John D. Ruby; Charles F. Cox; Naotake Akimoto; Nobuko Meada; Yasuko Momoi (International Journal of Dentistry)
This historical treatise follows the documented timeline of tooth decay into today's understanding, treatment, and teaching of caries biology. Caries has been attributed to many different causes for several millennia, however, only since the late 1900s has research revealed its complex multifactorial nature. European writers of the 1600s to 1700s held views that general health, mechanical injuries, trauma, and sudden temperature changes all caused caries—holding a common belief that decay was due to chemical agents, faulty saliva, and food particles. Until the early 1800s most writers believed that caries was due to inflammation from surrounding diseased alveolar bone. Today's science has demonstrated that caries is caused by indigenous oral microorganisms becoming a dynamic biofilm, that in the presence of fermentable sugars produce organic acids capable of dissolving inorganic enamel and dentin followed by the proteolytic destruction of collagen leaving soft infected dentin. As bacteria enter the pulp, infection follows.